STUDI PERBANDINGAN SIFAT MINYAK KAYU CENDANA SEMUT (EXOCARPUS LATIFOLIA R.BR.) DAN CENDANA WANGI (SANTALUM ALBUM L.) - Bambang Wiyono; Toga Silitonga (Jurnal Penelitian Hasil Hutan, 1990)
The  purpose of  this  research  is  to  compare the  oil. properties of  cendana   semut (Exocarpus latifolia R.Br.) and cendana wiangi (Santalum album  L.). The sandalwood   oils are obtained by  distillation   method   with  cohobation system for  18 hours.Results indicated that  the  essential  oil content of  cendana  semut is lower than  cendana wangi. The cendana semut oil had dark-yellow in colour and slightly thicker.   During the  early  stage  of  distilling  process, the  distillate of cendana semut some whitish  sediment  was formed, presumably consisted of resin. Such  sediment was not found  during  the distilling of  cendana wangi.  The  cendana  wangi oil had yellowish appearance and its viscosity was lower than that of cendana semut. Ester number  after acetylation and total  alcohol content (as santalol) of  cendana  semut oil was lower  than  of cendana wangi  oil.   Colour,  viscosity, and  resin content in  the distillate could be used to differentiate    cendana  semut from  cendana  wangi oil.